Popculture mechanisms of creating the worlds of the past. Cultural heritage in contemporary exhibition practices - Nieroba, Elżbieta (Studia Etnologiczne i Antropologiczne, 2012)
The memory of the past in a modern society finds its shelter in the walls of lieux de memoire, such as libraries, archives or museums. It is these institutions that we shift our responsibility for registering and storing everything that should be retained for future generations on. From this perspective, a museum can be perceived as a unit responsible for creating a social definition of heritage. Museologists, tidying a local, regional or national memory in an exhibition space, impose the vision of events and evaluation of past achievements on the audience. In a conscious or unconscious way, they participate in defining the truth about the past biding in a particular historical moment. A careful observation of changes happening in ways and styles of life in societies of late modernity shows limitations resulting from the Enlightenment museum discourse. A postmodernist blurring of a borderline between a high and low culture constitutes a starting point for going beyond fixed modes of thinking about museums as just dignified art institutions and temples of knowledge, and facilitates search for new tools in order to create a museum discourse using popular culture. Thus, museologists make efforts to make new exhibition arrangements adjusted to the present‑day expectations of the audience building and supporting bonds with the visitors, encouraging for discovering a potential of the artefacts presented, stimulating for a discussion with a suggested vision of the world or, generally speaking, to encourage undertaking cultural practices.